Highly Selective Removal of Perfluorinated Contaminants by Adsorption on All‐Silica Zeolite Beta. (26th May 2020) - Van den Bergh, Matthias; Krajnc, Andraž; Voorspoels, Stefan; Tavares, Sergio Rodrigues; Mullens, Steven; Beurroies, Isabelle; Maurin, Guillaume; Mali, Gregor; De Vos, Dirk E.
Abstract: Perfluorinated alkylated substances (PFASs) are widely used in industrial and commercial applications, leading to a widespread occurrence of these persistent and harmful contaminants in our environment. Removal of these compounds from surface and waste waters is being mandated by European and U.S. governments. Currently, there are no treatment techniques available that lower the concentrations of these compounds for large water bodies in a cost‐ and energy‐efficient way. We hereby propose a hydrophobic, all‐silica zeolite Beta material that is a highly selective and high‐capacity adsorbent for PFASs, even in the presence of organic competitors. Advanced characterization data demonstrate that the adsorption process is driven by a very negative adsorption enthalpy and favorable steric factors. Abstract : Perfluorinated compounds have found wide application but have adverse effects on health and environment. There is a need to selectively recover them from process and surface waters. We now show that a microporous zeolite Beta, in its all‐silica form, shows outstanding capacity and affinity for the uptake of PFASs like perfluorooctanoic acid and perfluorooctanesulfonic acid, even in the presence of other organics.